Mechanisms linking affective reactions to competition-related and competition-extraneous concerns in male martial artists - Cerin, E.; Barnett, A. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The main aim of this study was to examine affective linkages between competition-related and competition-extraneous concern domains. A secondary purpose was to establish the contributions of pre-competition affects to post-competition performance appraisals, independent of pre-competition performance expectations. Thirty-nine highly skilled male martial artists were assessed at five random times a day for a week and 1 h before a major competition on affective states and sources of concern. They also reported their performance expectations and post-competition performance appraisals. Affective states triggered by competition-related and competition-extraneous concerns persisted in time. Carry-over effects were stronger after reports of competition-related concerns, emphasizing the subjective importance of the competitive event. Although positive (enjoyment and surprise) and negative (sadness and guilt) affective spill-over was observed from competition-extraneous to competition-related concerns, the reverse held true only for disgust. These findings may be due to the athletes' ability to regulate affective reactions within a sporting setting, in particular. Spill-over from competition-extraneous to competition-related concerns is indicative of a lesser degree of control over work/study and family life. Given that average weekly negative affects and anger/disgust were independent predictors of post-competition performance appraisals, the phenomenon of spill-over and other affective linkage mechanisms in sport warrant further investigation.